2017
DOI: 10.1111/2041-210x.12914
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evolutionary patterns in bipartite networks: Vicariance, phylogenetic tracking or diffuse co‐evolution?

Abstract: Many pairwise interactions in ecological communities are thought to be structured by co‐evolution, a process difficult to study on a community level. Traditional methods can reveal correlated phylogenies between interacting organisms, suggesting a co‐evolutionary association. However, several processes could lead to cophylogeny, including (1) vicariance, (2) phylogenetic tracking and (3) co‐evolution. We present a framework to investigate diffuse co‐evolution between groups of interacting taxa. Our methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 67 publications
(117 reference statements)
1
43
0
Order By: Relevance
“…29 Ma, 95% HPD = 19–40 Ma; Kahnt et al, ). Moreover, our findings are in agreement with Russo et al (), who analysed 13,106 unique plant–pollinator interactions and found that vicariance or phylogenetic tracking of one taxon by its interaction partner underlay cospeciation events more often than co‐evolution.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…29 Ma, 95% HPD = 19–40 Ma; Kahnt et al, ). Moreover, our findings are in agreement with Russo et al (), who analysed 13,106 unique plant–pollinator interactions and found that vicariance or phylogenetic tracking of one taxon by its interaction partner underlay cospeciation events more often than co‐evolution.…”
Section: Discussionsupporting
confidence: 93%
“…However, cospeciation might result either (a) from the mutual interaction and reciprocal evolution of interacting populations (strict co‐evolution), (b) from a common biogeographic event that causes the subdivision of the distribution range of both interaction partners which causes them to simultaneously speciate (vicarance), or (c) when one taxon tracks the evolution of its partner and speciates in response to speciation events of its partner (phylogenetic tracking, De Vienne et al, ). We used the approach suggested by Russo, Miller, Tooker, Bjornstad, and Shea () to distinguish between these three alternative hypotheses, (a) co‐evolution, (b) vicariance or (c) phylogenetic tracking, as underlying cause for phylogenetic congruence and cospeciation. Specifically, Russo et al () used a Mantel test to investigate whether phylogenetic relatedness is correlated with ecological similarity, i.e., whether closely related pollinator or plant species are more likely to interact with similar partners than expected by chance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations